THE EFFECT OF PHYSICAL SERVICESCAPE, SOCIAL SERVICESCAPE, AND CONSUMER SATISFACTION ON REPURCHASE INTENTION IN THE FOOD AND BEVERAGE INDUSTRY - Honesta, Mellisa; C. Efrata, Tommy (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
The culinary business generally tends to have a short lifespan; therefore, effective strategies are needed to ensure sustainability and competitiveness. This research aims to examine the influence of physical and social servicescape on repurchase intention at Café Rindu Lokaria, with customer satisfaction as an intervening variable. Café Rindu Lokaria has operated in the food and beverage industry since 2016 and has implemented both physical and social servicescape concepts in its operations. The population of this study consists of customers who have made at least two transactions at the café. The sample was obtained using a purposive sampling technique, resulting in 215 respondents. Data were collected through an online questionnaire distributed via Google Forms. The data were analyzed using quantitative methods with the Structural Equation Modeling (SEM) approach, processed through SmartPLS 3.0 software. The research findings indicate a partial mediation effect, suggesting that physical and social servicescape can influence repurchase intention both directly and indirectly through customer satisfaction.